Principles of administrative rule-making are in Ukraine as areas of legal science - Svetlana Grechana (Kazimierz Wielki University, 2020)
The article is sanctified to research of the administrative rule-making, as areas of legal science that comes forward as the objective phenomenon. It is reflected, administrative rule-making in two values, as an area of legal science and as industry of legislation and their signs are described. Thus, it is marked that the administrative rule-making, as an area of legal science examines a legislation and judicial practice of his application that gives possibility is more deep to get to know principles of this sphere of public relations.